2013
DOI: 10.1073/pnas.1216841110
|View full text |Cite
|
Sign up to set email alerts
|

Variants at serotonin transporter and 2A receptor genes predict cooperative behavior differentially according to presence of punishment

Abstract: Punishment of free-riding has been implicated in the evolution of cooperation in humans, and yet mechanisms for punishment avoidance remain largely uninvestigated. Individual variation in these mechanisms may stem from variation in the serotonergic system, which modulates processing of aversive stimuli. Functional serotonin gene variants have been associated with variation in the processing of aversive stimuli and widely studied as risk factors for psychiatric disorders. We show that variants at the serotonin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Our study was constrained to a single population and a specific developmental stage; however, our results are corroborated by associations between the short allele and heightened sensitivity to social stimuli [13 -16], as well as altered anatomy and functionality in the brain's imitation circuitry [18,19]. Beyond social sensitivity, a vast literature on 5HTTLPR indicates that the short allele is related to diverse phenomena, including: empathy [27], cooperation [28] and dancing [29]. Following Canli & Lesch's [9] suggestion that 5HTTLPR, in interaction with the environment, may influence social behaviour by modulating neural activation in brain regions containing mirror and Von Economo neurons, we note that many seemingly unrelated observations can be reconciled by conceptualization of Both production imitation and social mimicry may contribute to cumulative culture, which arises from highfidelity imitation and social processes including prosociality, group identification and teaching [3,4].…”
Section: Discussionmentioning
confidence: 70%
“…Our study was constrained to a single population and a specific developmental stage; however, our results are corroborated by associations between the short allele and heightened sensitivity to social stimuli [13 -16], as well as altered anatomy and functionality in the brain's imitation circuitry [18,19]. Beyond social sensitivity, a vast literature on 5HTTLPR indicates that the short allele is related to diverse phenomena, including: empathy [27], cooperation [28] and dancing [29]. Following Canli & Lesch's [9] suggestion that 5HTTLPR, in interaction with the environment, may influence social behaviour by modulating neural activation in brain regions containing mirror and Von Economo neurons, we note that many seemingly unrelated observations can be reconciled by conceptualization of Both production imitation and social mimicry may contribute to cumulative culture, which arises from highfidelity imitation and social processes including prosociality, group identification and teaching [3,4].…”
Section: Discussionmentioning
confidence: 70%
“…Atypical antipsychotic treatment blocking the 5HT2A receptor site was found to both effectively reduce aggressive behavior and to improve social competence in patients with schizophrenia. In a recent study, Schroeder et al also reported that the 5HT2A receptor gene was related to cooperative behaviors. Risperidone has also been found to enhance prosocial behavior in children with disruptive behavior and sub‐average IQ .…”
mentioning
confidence: 96%
“…Previous studies have shown these to be important predictors of contributions [41,62]. Ordered logit and binomial models were also considered but resulted in little change in predictions (see [63] for results); thus, for all subsequent analyses, we used the Gaussian model.…”
Section: (D) Statistical Analysesmentioning
confidence: 99%